A study on life cycle of maintenance during the in use phases of flexible pavement from Pagoh to Machap - Mohd Yunus, Mohamad Yazid; Ali, Maisarah (IIUM Press, International Islamic University Malaysia, 2017)
Preventive maintenance on pavement is very important to prolong life for both functional and structural strength performance in order to provide comfortable and safe riding to traffics. It is easier and cheaper to repair the pavement surface in time, so that serious damage of the pavement structure is avoided. Delaying or neglecting the road maintenance activities may increase the overall cost of repair and also affect the vehicle operating cost for the road user. In order to find the right balance to reduce the repair and maintenance cost the research involved case study of the 70km section of the North South Interurban Toll Expressway from Pagoh to Machap. The aim of the study is to present the total repair and maintenance cost incurred over a period of 20 years. Various treatment methods have been adopted such as mill and replace, overlay, overlay with pre-treatment and regulating works. The result from life cycle cost analysis indicated that the cost of maintenance and repair of this stretch of expressway is considerably low. Compared to the initial construction cost, the maintenance and repair constitute to only about 7.4% of the initial construction cost. The maintenance cost indicates the high quality of the design and initial construction, and an effective preventive maintenance and repair process performed by the road owner.